Muborak@gmail.com STYLISTIC FUNCTION OF COLOUR TERMS: STYLISTIC FUNCTION OF COLOUR TERMS - Turayeva, Muborak (Журнал иностранных языков и лингвистики, 2022)
The colour terms possess a very distinct feature of emotiveness. In a literary text and in speech they are mostly used as details, the emission of which does not generally break the content-factual information (OFI) conveyed by the context. The use of colour notions in a text adds mainly to its content-conceptual information (CCI), i. e. - it conveys the author’s individual understanding and the emotional attitude to the things described by means of OFI, being an important component of the language modality.